Possible Involvement of Foxp3(+) Regulatory T Cells in the Development of Immune-Mediated Pancreatitis in MRL/Mp Mice Treated with Polyinosinic:Polycytidylic Acid - Koyabu, Masanori (Hindawi Publishing Corporation, 2013)
Objectives. This study was conducted to clarify whether or not Tregs are involved in the development of immune-mediated pancreatitis in MRL/Mp mice as an AIP (autoimmune pancreatitis) model, in order to understand more clearly the pathogenic mechanism of AIP. Methods. We compared the immunohistochemical features of pancreatic forkhead box P3 (Foxp3) in the administration of poly I:C in MRL/Mp mice and two types of control mice (BALB/c and C57BL/6). As a contrast, we analyzed three mouse models of pancreatitis without autoimmune mechanism (Cerulein-, Ligation-, and Ligation + Cerulein-treated mice). After staining these specimens, we compared the ratios of Foxp3-positive cells to infiltrated mononuclear cells (Foxp3/Mono). Results. Our immunohistochemical study of Foxp3 revealed that the infiltration of Foxp3-positive cells increased in poly I:C-treated MRL/Mp mice. The histopathological score of pancreatitis showed no difference among poly I:C-treated MRL/Mp, Ligation-, and Ligation + Cerulein-treated mice; however, the Foxp3/Mono ratio in poly I:C-treated MRL/Mp mice was significantly increased compared with Ligation- and Ligation + Cerulein-treated mice. Conclusions. MRL/Mp mice treated with poly I:C showed early development of pancreatitis with abundant infiltration of Foxp3-positive cells. There may be a possibility that Tregs are involved in the development of pancreatitis in these mice.